Development of the Chinese Milk-Tea Market in Informatization - Wang, Pengsen (2024)
This paper makes use of enterprise management, marketing theory, consumer behavior and other related knowledge. The paper analyzes the development status of milk tea industry in China, milk tea consumers, and the problems that will be faced in the development process of milk tea industry. First of all, PEST model will be used to analyze the macro environment of milk tea industry, which mainly includes four aspects: politics, economy, social culture and technology. After analyzing the macro environment of the milk tea industry market, the internal and external influencing factors are analyzed with SWOT analysis tool. Under the background of information technology, this paper analyzes the innovative method of milk tea marketing model and summarizes how to use this method for innovation in the development of China's milk tea industry. Milk tea industry is an industry with easy homogenization and fast iteration speed. This paper will show that milk tea chain industry can expand innovative ideas through case analysis and make innovative breakthroughs through scene value chain research.